THE ROLE OF BiPO4 INTRODUCED THROUGH THE GAS PHASE IN THE PROCESS OF CREATING THIN FILMS ON THE SURFACE OF InP - Kostryukov Victor F.; Mittova Irina Y.; Sladkopevtsev Boris V.; Parshina Anna S.; Balasheva Dar’ya S. (Конденсированные среды и межфазные границы, 2019)
Purpose. The purpose of this work was to establish the infl uence of bismuth phosphate introduced through the gas phase on the InP thermal oxidation process and the determination of the composition of the formed fi lms. Methods and Methodology.Oxidation was performed on (100)-oriented polished single-crystal indium phosphide wafers (with a concentration of main charge carriers at 300 K of at least 5×1016 cm–3 and intrinsic n-type conductivity). The oxidation of InP was conducted at 475, 500, 530, and 550 °С in 30 L/h oxygen for 10–60 min using postoxidation. The thickness of the formed oxide fi lms was determined by laser ellipsometry (l = 632.8 nm) with an absolute error of ±1 nm. Results.The accelerating effect of bismuth phosphate on the process of fi lm formation was established. The magnitude of the acceleration is from 1.5 to 2 times and the maximum fi lm growth is achieved in the fi rst 10 min of oxidation. The transit mechanism of action of BiPO4 was established. The determining process is the formation of indium phosphate due to the secondary interaction of the oxide forms of the components of the substrate. The limiting stage is the diffusion of oxides in the solid phase, as evidenced by the values of n (0.22) and EEA (188 kJ/mol). The authors established a decrease in the EEA compared with the process of InP’s own thermal oxidation, which provides the accelerated formation of a fi lm on the surface of a semiconductor with chemostimulated thermal oxidation. IR spectroscopy, EPXMA, and X-ray phase analysis were used to study of fi lms on the surface of InP. The main components of the fi lms on the InP surface are indium oxide and indium phosphates of different composition. With an increase in temperature and oxidation time, the content of indium oxide in fi lms decreases, and the variety and amount of indium phosphates increases. Conclusions.This indicates the transformation of some phases to others during solid phase transformations and corresponds to the consumption of indium oxide during secondary processes in the fi lm without a signifi cant increase in its thickness. Bismuth phosphate plays the role of a chemostimulator of the thermal oxidation process of InP and may be a modifi er of the composition, and hence the properties of fi lms on its surface.